A Framework for Supporting Simulation with Normative Agents - Viana, Marx; Cunha, Francisco; Santos Neto, Baldoino; Alencar, Paulo; Lucena, Carlos J. P. de (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2015)
Multi-agent systems are societies in which autonomous agents work to achieve both common and individual goals. In this context, norms have been used as mechanisms to regulate the behavior of such agents and ensure a desirable social order where agents can work together. Although norms are a promising mechanism, it is necessary to evaluate the positive and negative impact of using them. Therefore, this work presents a framework for normative multi-agent systems simulation that provides the mechanisms necessary to understand the impact of norms on agents and the society they belong to.